Effect of naphthalene acetic acid on sprouting and rooting of stem cutting in Mussaenda species - Rashid, MHA; Nahar, A (Progressive Agriculture, 2019)
Mussaendas are increasingly popular for the showy colour they provide during much of the year in garden landscapes. However, root formation in stem cuttings is a major challenge for cultivation of Mussaenda species. Therefore, the experiment was carried out at the Landscaping section of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh during the period from August to November 2018 to study the effect of phytohormone naphthalene acetic acid (NAA) on sprouting and rooting of stem cuttings in Mussaenda species. The two-factor experiment consisted of three Mussaenda species viz., Mussaenda frondosa (White flag bush), Mussaenda philippica (Pink flag bush) and Mussaenda erythrophylla (Red flag bush), and five concentrations of NAA viz., 0 (control), 0.1%, 0.2%, 0.3% and 0.4%. The experiment was laid out in randomised complete block design (RCBD) with three replications. The results revealed that all the traits related to sprouting and rooting potential of stem cuttings were significantly influenced by combined effects of Mussaenda species and various NAA concentrations. The maximum sprouted bud per cutting (3.57), highest number of roots per cutting (5.88) and the longest root length (4.32 cm) were recorded from M. philippica except number of leaves per stem cutting (4.42) in M. erythrophylla. The increasing concentrations of NAA application responded positively on sprouting and rooting characters in all three Mussaenda species used for this experiment. The best results obtained from the treatment where NAA was applied at the concentration of 0.3% with 3.92 sprouted buds per cutting, 4.77 leaves per cutting, 7.15 roots per cutting and 5.26 cm length of roots. The treatment combination of M. philippica (Pink flag bush) and 0.3% NAA, followed by NAA at 03% with M. erythrophylla (Red flag bush) was found to be best in terms of sprouting and rooting of stem cuttings in Mussaenda. Progressive Agriculture 30 (1): 48-54, 2019